Impression Management Perempuan Perokok Di Kota Banda Aceh - Deni Yanuar; Nur Anisah; Maini Sartika; Revita Rahman (President University, 2021)
This study is entitled “impression management female smoker in Banda Aceh city”. This study is describes how female smoker role to the society and people she meets. This study aimed to find out impression management female smoker, and to know frontstage and backstage female smoker of interacting with society in Banda Aceh city. Dramaturgy theory is used in this study. The approach used in this study is a qualitative descriptive method. The technique of determining informants used by researchers is purposive sampling technique. The research subjects are 3 informants who is female active smoker and stay in Banda Aceh city. The data collection techniques used are observation, interviews and documentation, By using interactive model analysis techniques, namely data reduction, data display, and making decisions. The result of the research shows that, female smoker plays a role to keep her identity as female smoker unknown by people like family, friends, and client. Although they often met with less pleasing views and behaviors in society, female smoker does not care about that thing. In impression management, there are some indicators that can be examined for how the female smoker’s role is involved in her daily life, including, appearance, locution, friendships, and location. This study is expected to increas reference to next research. The study is also expected to make the public aware that not all girlseho smoke are bad women. And also alert female smokers that smoking is not good for their health and for others.